Significantly enhanced UV-light-driven photocatalytic performance of ferroelectric (K0.5Na0.5)NbO3: Effect of corona-poling and particle size. (August 2022) - Kujur, Vidya Spriha; Gaur, Roopam; Gupta, Vaishali; Singh, Satyendra
Abstract: This work focuses on the effect of corona-poling and particle size on photocatalytic performance of (K0.5 Na0.5 )NbO3 (KNN) ferroelectric powder synthesized by solid-state reaction (sample abbreviated as "KNN-cera") and sol-gel (sample abbreviated as "KNN-nano") techniques. Results show that degradation efficiencies of RhB solution under UV light irradiation with ferroelectric KNN-cera (average particle size: 1.21 μm) and KNN-nano (average particle size: 0.197 μm) poled under 1.5 kV/mm field were 89.5% and 96.5% whereas for unpoled KNN-cera and KNN-nano samples it was 29.4% and 86.09% respectively. The KNN-nano sample has shown better photocatalytic activity due to smaller size of the calcined powder. Corona poling treatment given to the synthesized powder displays a great influence on the photocatalytic activity due to enhancement in internal polarization field that makes photogenerated free electrons and holes move in the opposite directions, resulting in the spatial separation of free electrons and holes providing them with more time to participate in surface reactions. This helps in achieving better photocatalytic performance. Graphical abstract: Image 1 Highlights: Photocatalytic activity of KNN powder enhanced due to Corona poling. Enhanced photocatalytic activity in KNN-nano sample due to large surface area. Degradation efficiency of RhB solution for KNN-cera (solid state) was 89.5%. Degradation efficiency of RhB solution for KNN-nano (sol-gel) was 96.5%. Reusability of KNN powder obtained post catalytic treatment was confirmed by XRD.